Selection from Many Investments with Managerial Private Information* - ANTLE, RICK; BOGETOFT, PETER; STARK, ANDREW W. (Contemporary Accounting Research, 1999)
Abstract We investigate capital investment problems when a manager knows the costs of a set of available projects, while the owner only holds probabilistic beliefs about these costs. With mutually exclusive projects, an optimal policy can be defined by a series of cost targets, one for each of the possible projects. The project with the lowest reported cost relative to the target is chosen, and funded as if the cost were equal to the target. The optimal investment policy can deviate from a traditional policy of selecting the project with the highest, positive net present value (NPV) in a number of ways. First, under‐investment arises to limit the manager's ability to capture the economic rents. Second, when investment takes place, it is not always the project with the highest NPV that is implemented. Third, projects with lower cost variability can be favored. We extend the analysis to non‐mutually exclusive projects. With two independent projects, batch processing is superior to individual appraisal whenever both optimal individual appraisal cost targets are interior. Individual appraisal ignores the impact of individual targets on incentives to report the costs of other potential projects. Batch processing can improve individual assessment by cost effective switching of investment away from the individual projects and into the batch as a whole. The results suggest that the common practice of analyzing batches of capital requests in an annual capital budgeting cycle provides advantages in the organization's attempt to deal with asymmetric information and incentive problems.